Capital structure and profitability of Vietnamese commercial banks: Evidence from Monte Carlo simulation via the Bayes - Tran, Xuan Linh Nguyen; Tran, Thanh Nga Thi; Thi, Huong, Phan (Journal of Social Economics Research, 2025)
The objective of this study was to investigate the existence of an optimal capital structure for commercial banks. The authors employed a Bayesian regression approach to analyze the data gathered from 24 listed commercial banks in Vietnam from 2011 to 2021. The findings prove the existence of the optimal capital structure of banks. Furthermore, the study underscores the significance of bank size in enhancing overall bank performance and reveals that inflation positively affects bank profitability. Leveraging the advantages of the Bayesian methodology for small sample data analysis, the authors introduced a framework for estimating the optimal capital structure for individual banks. In this context, two banks were selected for case studies: Asia Commercial Bank (ACB) and Vietnam Joint Stock Commercial Bank for Industry and Trade (CTG). The analysis indicated that both banks maintain a deposit-to-total assets ratio that exceeds the optimal threshold and should consider adjustments to bring this ratio down. Conversely, the non-deposit to total assets ratio for both banks remains relatively low, suggesting a potential for an increase in order to optimize their financial performance.